ANALISIS PESAN DAKWAH DALAM KONTEN AKUN INSTAGRAM @MUHAMMADNUZULDZIKRI - andriyani, yunita; Siti Misbah; Rasman (JOISCOM (Journal of Islamic Communication), 2024)
Da'wah, the activity of inviting and urging people towards good (ma'ruf) andaway from evil (munkar), is a significant aspect of Islam. Today, da'wah is not only delivered from the pulpit but also through social media, such as Instagram. This study aims to explain the content of da'wah messages in motion graphic videos found on the Instagram account @muhammadnuzuldzikri during the period from June 2023 to November 2023. The theories used in this research are Samsul Munir Amin's theory of da'wah messages and the content analysis theoriesof Neuendorf and Krippendorff. This research employs a descriptive qualitative approach using content analysis methods. Based on the results of the study, therewere 19 motion graphic videos during the period from June 2023 to November 2023. These videos contained three categories of da'wah messages: aqidah(faith), sharia (Islamic law), and akhlaq (morality). Within these three categories, several types of messages were identified. In the aqidah category, there were four messages about faith in Allah SWT, faith in the Prophet Muhammad (peace beupon him), faith in the holy books of Allah SWT, and faith in Qadha and Qadar. In the sharia category, there were eight messages about dhikr (remembrance) of Allah SWT, remembering Allah in the month of Al-Muharram, practicing the Sunnah of the Prophet in the month of Al-Muharram, practicing the fast of Ashura, practicing Sunnah fasting, practicing fasting on the 9th of Al-Muharram, the deeds of those who will sacrifice, and the deeds on the day of Arafah. In the akhlaq category, there were seven messages about morality towards Allah SWT, morality towards oneself, and morality towards fellow humans. Keywords: Content analysis, Instagram, Motion graphic, Da'wah messages